2012
DOI: 10.1371/journal.pone.0032240
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Trunk Stability in Individuals at High Risk for Parkinson's Disease

Abstract: BackgroundThe search for disease-modifying treatments for Parkinson's disease advances, however necessary markers for early detection of the disease are still lacking. There is compelling evidence that changes of postural stability occur at very early clinical stages of Parkinson's disease, making it tempting to speculate that changes in sway performance may even occur at a prodromal stage, and may have the potential to serve as a prodromal marker for the disease.Methodology/Principal FindingsBalance performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
79
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 36 publications
4
79
1
Order By: Relevance
“…All participants were investigated in the frame of the PMPP study (Progression Markers in the Premotor Phase of PD) 14 26. This study comprises a population of 16 patients with PD in early disease stages, 40 individuals supposed to be at high risk for PD (see below), and 14 controls with no risk marker for PD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants were investigated in the frame of the PMPP study (Progression Markers in the Premotor Phase of PD) 14 26. This study comprises a population of 16 patients with PD in early disease stages, 40 individuals supposed to be at high risk for PD (see below), and 14 controls with no risk marker for PD.…”
Section: Methodsmentioning
confidence: 99%
“…The start of the PD-specific neurodegenerative process may even be years to decades earlier than the characteristic motor symptoms which enable clinical diagnosis of PD. This prodromal phase is associated with an increased probability to have non-motor signs or symptoms (eg, hyposmia,7 8 rapid eye movement (REM), sleep behaviour disorder,9–11 depression,12 constipation12 13) and/or slight motor symptoms (eg, reduced arm swing, trunk instability,14 stiffness and slowness not sufficient for the diagnosis of PD but increasing the likelihood for its future onset15–17), and/or imaging abnormalities (eg, enlarged hyperechogenic substantia nigra18–20). However, the non-motor signs are not specific for PD as they are frequently present in the elderly population or co-occur with other diseases 21.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 It leads to loss of mobility, disability, and reduced quality of life. 5,6 Recent studies have shown that PI begins early after disease onset, 7,8 with around one third of individuals developing PI within the first 2 years after diagnosis. 5 Postural instability affects balance control in PD mainly in 4 domains: (1) balance during quiet stance, (2) reactive postural adjustments to external perturbations, (3) anticipatory postural adjustments, and (4) dynamic balance.…”
Section: Introductionmentioning
confidence: 99%
“…Accelerometers have been used to assess postural control 24 in older adults and to identify early symptoms of Parkinson disease. 25 A low-cost tool that quantifies postural sway using an accelerometer was developed by team members at the University of Pittsburgh. 26 A dual-axis accelerometer (ADXL213AE, 61.2 g; Analog Devices, Inc., Norwood, MA) was chosen for its low-frequency characteristics and because it was designed to optimally record mediolateral and anteroposterior acceleration of the pelvis/trunk during standing.…”
mentioning
confidence: 99%